Stress-Responsive cis-Regulatory Elements Underline Podophyllotoxin Biosynthesis and Better Performance of Sinopodophyllum hexandrum Under Water Deficit Conditions - Kumari, Anita; Dogra, Vivek; Joshi, Rohit; Kumar, Sanjay (Frontiers in Plant Science, 2022)
Sinopodophyllum hexandrum is an endangered medicinal herb known for its bioactive lignan podophyllotoxin (PTOX), which is used for preparation of anti-cancer drugs. In natural habitat, S. hexandrum is exposed to a multitude of adversities, including temperature extremes and fluctuations, water deficit, and UV radiations. Transcriptional regulation of genes, which is regulated by the condition-specific binding of transcription factors to the precise motifs in the promoter region, underlines the responses to an environmental cue. Therefore, analysis of promoter sequences could ascertain the spatio-temporal expression of genes and overall stress response. Unavailability of genomic information does not permit such analysis in S. hexandrum, especially on regulation of PTOX pathway. Accordingly, the present work describes isolation and in silico analysis of 5′-upstream regions of ShPLR (PINORESINOL-LARICIRESINOL REDUCTASE) and ShSLD (SECOISOLARICIRESINOL DEHYDROGENASE), the two key genes of PTOX biosynthetic pathway. Data showed a range of motifs related to basal transcription, stress-responsive elements, including those for drought, low temperature, and light, suggesting that expression of these genes and resulting PTOX accumulation would be affected by, at least, these environmental cues. While the impact of temperature and light on PTOX accumulation is well studied; the effect of water deficit on physiology of S. hexandrum and PTOX accumulation remains obscure. Given the presence of drought-responsive elements in the promoters of key genes, the impact of water deficit was studied on growth and development and PTOX accumulation. Results showed a declining relative water content and net photosynthetic rate, but increased relative electrolyte leakage with stress progression. Plants exhibited a reduction in transpiration rate and chlorophyll content, with a gradual increase in osmoprotectants. Besides, stressed plants showed increased expression of genes involved in the phenylpropanoid pathway and PTOX biosynthesis, and an increase in PTOX accumulation. Upon re-watering, non-irrigated plants showed a significant improvement of biochemical and physiological parameters. Summarily, our results demonstrated the importance of osmoprotectants during water deficit and the revival capacity of the species from water deficit, wherein PTOX synthesis was also modulated. Moreover, isolated promoter sequences could be employed in the genetic transformation to mediate the expression of stress-induced genes in other plant systems.